2014
DOI: 10.1002/14651858.cd000103.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Haemodilution for acute ischaemic stroke

Abstract: BackgroundIschaemic stroke interrupts the flow of blood to part of the brain. Haemodilution is thought to improve the flow of blood to the affected areas of the brain and thus reduce infarct size. ObjectivesTo assess the effects of haemodilution in acute ischaemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 66 publications
1
24
0
Order By: Relevance
“…Therapies such as haemodilution, related to low osmolarity, was adopted in patients with stroke, but the conclusion remains controversial. 27–29 Further studies are needed to investigate the interactions among serum osmolarity, osmotherapy and mortality in this subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…Therapies such as haemodilution, related to low osmolarity, was adopted in patients with stroke, but the conclusion remains controversial. 27–29 Further studies are needed to investigate the interactions among serum osmolarity, osmotherapy and mortality in this subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is possible that administration of exogenous albumin or albumin-oleic acid may confer some benefits for MS similar to the preclinical results described above for other conditions, high dose albumin therapy has been tested in clinical trials for ischemic stroke but was found to have no benefit, and it even increased mortality in subjects that were > 83 years old [ 173 ]. The increased mortality in elderly individuals was suggested to be due to increased myocardial stress [ 174 ]; of note, there is evidence to suggest that MS patients have a greater risk for myocardial infarction [ 175 ].…”
Section: Reviewmentioning
confidence: 99%
“…Cerebral blood volume augmentation by plasma expansion and haemodiluition could improve cerebral perfusion in experimental stroke models [ 46 ]. However, in acute stroke trials performed in the 1990s, plasma expansion by dextran 40 and hydroxyethyl starch showed no benefit on neurological outcome or mortality [ 47 ]. Notably, all these early clinical studies were performed in the pre-thrombolysis era and outside a meaningful therapeutic window (patients were enrolled many hours or even days after symptom onset) and cerebral collateral flow was not assessed.…”
Section: Acute Therapeutic Modulation Of Cerebral Collateral Flowmentioning
confidence: 99%